2004
DOI: 10.1063/1.1741025
|View full text |Cite
|
Sign up to set email alerts
|

Propagation loss in GaN-based ridge waveguides

Abstract: GaN ridge waveguides were fabricated by selective area growth in an organometallic vapor phase epitaxial system. The growth enhancement on a 3.5 μm wide exposed channel versus the masked area width was measured. The propagation losses of a series of GaN multimode waveguides, with different widths, were measured by the outscattering technique at λ=488 nm. The internal optical loss of the GaN ridge waveguide was found to be αint∼4.45 cm−1. Sidewall scattering loss (αscat) and the additional optical loss due to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…The optical loss is mainly due to light scattering by etched sidewalls of the waveguide and can be minimized through techniques such as wavelength selective coating, gentle wet etching following plasma etching, etc. This measured value of optical loss in Er-doped GaN devices is smaller than an earlier reported value of 4.45 cm −1 for undoped GaN ridge waveguide devices measured at visible ͑488 nm͒ wavelength 15. The small value of optical loss in GaN:Er waveguide is what we expected because 1.54 m wavelength is far from the band gap of the guiding medium, GaN ͑362 nm͒.…”
contrasting
confidence: 70%
“…The optical loss is mainly due to light scattering by etched sidewalls of the waveguide and can be minimized through techniques such as wavelength selective coating, gentle wet etching following plasma etching, etc. This measured value of optical loss in Er-doped GaN devices is smaller than an earlier reported value of 4.45 cm −1 for undoped GaN ridge waveguide devices measured at visible ͑488 nm͒ wavelength 15. The small value of optical loss in GaN:Er waveguide is what we expected because 1.54 m wavelength is far from the band gap of the guiding medium, GaN ͑362 nm͒.…”
contrasting
confidence: 70%
“…During the operation of waveguides, the optical losses of light injected into the waveguide are also a critical parameter. 17 The smaller the losses in the GaN structure, the better the performance of the waveguide device in transmitting light. By injecting light through a prism with the Metricon setup, we measured the propagating wave intensity in the GaN layer wherein we excite the fundamental effective guided mode in this layer.…”
mentioning
confidence: 99%
“…Various optical components have already been demonstrated based on the III‐N material system, including arrayed waveguide gratings , directional couplers , all‐optical modulators and more . Previous studies, using various techniques and designs, reported propagation losses of GaN based WGs ranging from about 10 to more than 100 dB/cm . These values are much worse than the losses encountered when using Si or other III‐V materials (e.g., GaAs and InP), which are a few tenths of dB/cm .…”
Section: Introductionmentioning
confidence: 99%